ROLE IN HOUSE TRAINING AND ACADEMIC SUPERVISION IN IMPROVING TEACHER PERFORMANCE IN HIGH SCHOOL - Yudi Kirmadi; Bambang Ismaya; Maman Suryaman (RADJA PUBLIKA, 2026)
Education is a dynamic sector that continually undergoes policy changes in line with societal demands and the pace of global development. These policy shifts directly impact the role of teachers, both in their pedagogical functions and in maintaining professional standards. Teachers are required to adapt to new regulations to perform their duties effectively. Failure to adapt may lead to decreased performance, ultimately affecting the quality of classroom learning. The implementation of the Merdeka Curriculum, which adopts a deep learning approach, demands teachers to adjust their competencies to carry out learning activities in accordance with its requirements. To address these challenges, the school implements In House Training (IHT) and academic supervision as strategies for professional teacher development. This study aims to analyze the role of IHT and academic supervision in improving teacher performance in the domain of pedagogical competence across three key aspects: lesson planning, instructional implementation, and learning evaluation. This research employs a qualitative case study approach, with data collected through in-depth interviews, classroom observations, and document analysis. The main informants include school supervisors, the school principal, the vice principal for curriculum, and teachers. The results indicate that IHT significantly enhances teachers’ understanding of lesson plan development, differentiated instruction, and formative assessment. Meanwhile, academic supervision ensures the implementation of these competencies through pre-observation, classroom observation, reflection, and follow-up activities. Overall, there is a substantial improvement in teachers’ abilities to design relevant instructional materials, apply active learning strategies, utilize digital media, and conduct more systematic learning assessments.